Effect of Colchicine and Bio-catharantin on the DNA Relative Content and Stomatal Structure of Black Rice (Oryza sativa L. var. Jeliteng) - Dwi Setyati; Mukhamad Su’udi; Dyah Retno Wulandari; Tri Handoyo; Fuad Bahrul Ulum (Universitas Sebelas Maret, 2024)
Black rice (Oryza sativa L. var. Jeliteng), known for its health benefits compared to white rice, faces challenges in productivity. Among varieties, this black rice is popular in Indonesia but shows low yield. Research on improving black rice through genetic manipulation with antimitotic substances is limited. Therefore, this study aims to compare the effects of colchicine and Bio-catharantin on the germination rate, DNA relative content, and stomatal structure of O. sativa L. var. Jeliteng. Seeds were treated with colchicine (0.1%, 0.2%, and 0.3%) and Bio-catharantin (0.1%, 0.2%, 0.3%, 0.4%, and 0.5%) at soaking durations of 12, 24, and 48 hours. Germination was assayed, ploidy was determined using flow cytometry, and stomatal traits, including size and density, were examined microscopically. The results showed that Bio-catharantin did not exhibit any toxic effects on germination rates, whereas colchicine reduced germination starting at 0.2% concentration. Both chemical agents modified the DNA relative content of Jeliteng black rice. Colchicine generally increased stomatal length and width while decreasing stomatal density, with significant changes at 0.3% concentration for 24 hours. Bio-catharantin also altered stomatal traits, enhancing length and width in most cases but significantly reducing density under certain conditions. Bio-catharantin emerged as a promising alternative to colchicine for inducing chromosomal mutations in plants, offering benefits in altered stomatal structures without the toxic effects on germination, compared to colchicine.